Environmental, social, and governance or ESG scores: a case study for American Plains Co-op - Schmeidler, Dallas (Kansas State University, 2023)
Environmental, Social, and Governance, or ESG, scores are a new way for potential investors to judge the sustainability of a company. The main source of investor information in the past were limited to financial statements and other reported information such as operating goals and results, and management compensation. The traditional information, even if it is positive, does not always equal a safe or sustainable investment. As publicly traded companies begin exploring new ways to improve their own ESG score and prove their sustainability, it will begin affecting those companies throughout their supply chain. This study will research ESG scores and their presence in the agricultural industry to determine the importance of ESG scores at the local grain cooperative level, specifically to the American Plains Cooperative, a farmer owned cooperative in central Kansas and Northern Oklahoma.
Keywords: Environmental; Social; Governance; ESG score; Cooperative